Improving Auditors' Consideration of Evidence Contradicting Management's Estimate Assumptions - Austin, Ashley A.; Hammersley, Jacqueline S.; Ricci, Michael A. (Contemporary Accounting Research, 2020)
ABSTRACT Auditors have difficulty evaluating the assumptions underlying management's estimates. One source of these problems is that auditors appear to dismiss evidence contradicting management's assumptions because their initial preference to support management's accounting biases their preliminary conclusions and, thus, their interpretation of evidence. We experimentally examine whether auditors with a balanced focus (i.e., a focus on documenting evidence that supports and contradicts their preliminary conclusion) are less likely to dismiss evidence that contradicts management's assumptions than auditors with a supporting focus (i.e., a focus on documenting evidence that supports their preliminary conclusion). We expect and find that, compared with auditors with a supporting focus, auditors with a balanced focus create documentation that is less dismissive of evidence contradicting management's estimate. Importantly, a balanced focus changes auditors' cognition and affects how auditors interpret contradicting evidence rather than merely increasing their documentation of this evidence. The effects of reduced dismissiveness persist to improve auditors' evaluations of a biased estimate and subsequent actions, improving audit quality in an important and difficult area.